High-toughness anti-cracking PP (polypropylene) plastic and preparation process thereof

By adding modified natural fiber toughening agent, glass fiber and nano calcium carbonate to PP plastic, and adopting compounding and extrusion processes, the problem of insufficient toughness of PP materials is solved, and a high toughness and crack resistance is achieved. Improves the mechanical and environmental performance of the material.

CN119391080AInactive Publication Date: 2025-02-07JIEYANG HERCULES HOUSEHOLD PRODUCTS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411661497.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The toughness of PP materials is poor, especially in extremely harsh environmental conditions. The existing modification methods have limited effect on improving mechanical properties.

Method used

Using a high-tough crack-resistant PP plastic preparation process, including PP, POE, modified natural fiber toughening agent, glass fiber and nano calcium carbonate, the modified natural fiber toughening agent is obtained through physical modification and chemical modification, and the modified natural fiber toughening agent is obtained through Combination and extrusion processes produce high toughness and crack resistance PP plastics.

Benefits of technology

It significantly improves the tensile and impact resistance of PP plastic, enhances the overall toughness of the material, and has good compatibility and environmental protection.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a high-toughness anti-cracking PP plastic and a preparation process thereof, and belongs to the technical field of plastics. The invention discloses high-toughness anti-cracking PP (polypropylene) plastic, which is prepared from the following raw materials in parts by weight: 50 to 80 parts of PP (polypropylene), 20 to 35 parts of POE (polyolefin elastomer), 15 to 20 parts of modified natural fiber flexibilizer, 10 to 15 parts of glass fiber and 10 to 15 parts of nano calcium carbonate. The modified natural fiber toughening agent is obtained through physical modification and chemical modification, has excellent tensile property and impact resistance, and has good compatibility with PP. The modified natural fiber toughening agent and the glass fiber are compounded to synergistically enhance the toughness, the modified natural fiber toughening agent and the glass fiber are added into a PP and POE blended material, and meanwhile, nano calcium carbonate with rigidity is added for combined action, so that the high-toughness anti-cracking PP plastic can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastics and relates to a high-toughness and crack-resistant PP plastic and a preparation process. Background Art

[0002] Polypropylene (PP) is a semi-crystalline polymer with the characteristics of light weight, stable chemical properties and easy processing and molding. It is widely used in various fields of national economy and people's livelihood. However, the toughness of PP materials is poor, especially in extremely harsh environmental conditions. The toughening modification methods of PP include physical toughening, chemical toughening, β-nucleation toughening, fiber toughening and ultrasonic toughening. Among them, fiber toughening is achieved by adding natural fiber toughening agents. Fiber reinforcements can not only maintain the main properties of the matrix, but also obtain properties that the original components do not have.

[0003] Natural fiber is a renewable resource that can be recycled. It has a low density, low cost, and is environmentally friendly and pollution-free. Blending it with plastics and other products can greatly reduce costs while being harmless to the environment. Since the fiber molecules contain more hydrophilic hydroxyl groups, they need to be modified before blending with plastic products. The current methods for modifying it mainly involve surface treatment with silane coupling agents and oxidation treatment. However, the internal structure of the treated natural fiber is damaged to a certain extent, thus affecting the mechanical properties. Summary of the invention

[0004] The present invention relates to a high-toughness and crack-resistant PP plastic and a preparation process, and belongs to the field of plastic technology. The present invention discloses a high-toughness and crack-resistant PP plastic comprising the following raw materials in parts by weight: 50 to 80 parts of PP (polypropylene), 20 to 35 parts of POE (polyolefin elastomer), 15 to 20 parts of modified natural fiber toughening agent, 10 to 15 parts of glass fiber, and 10 to 15 parts of nano calcium carbonate. The present invention obtains a modified natural fiber toughening agent through physical modification and chemical modification, which has excellent tensile properties and impact resistance, and has good compatibility with PP. The modified natural fiber toughening agent is compounded with glass fiber to synergistically enhance toughness, added to PP and POE blended materials, and simultaneously added with rigid nano calcium carbonate to work together, so as to prepare a high-toughness and crack-resistant PP plastic.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-toughness and crack-resistant PP plastic comprises the following raw materials in parts by weight: 50-80 parts of PP (polypropylene), 20-35 parts of POE (polyolefin elastomer), 15-20 parts of modified natural fiber toughening agent, 10-15 parts of glass fiber and 10-15 parts of nano calcium carbonate.

[0007] Furthermore, the preparation method of the modified natural fiber toughening agent comprises the following steps:

[0008] (1) washing bagasse to remove impurities, adding water to heat and boiling;

[0009] (2) then cooling, adding a biological fermentation agent for fermentation, and obtaining a pre-product;

[0010] (3) adding a hydroxyl radical scavenger to the pre-product, mixing and stirring, filtering and drying to obtain product A;

[0011] (4) The product A is ground in a ball mill, sieved, added with a lubricant and stirred, and then vacuum dried to obtain a modified natural fiber toughening agent.

[0012] Furthermore, in the step (1), the mass ratio of bagasse to water is 2:3, the heating refers to heating to 98-100° C., and the boiling time is 20-30 min.

[0013] Furthermore, the cooling in step (2) refers to cooling to 30-40°C, the biological fermentation agent is yeast, and the yeast accounts for 1%-5% of the mass of sugarcane bagasse, the fermentation temperature is 25-35°C, and the fermentation time is 5-7 days.

[0014] Furthermore, in the step (3), the hydroxyl radical scavenger is potassium permanganate or sodium borohydride, and the hydroxyl radical scavenger accounts for 2% to 3% of the mass of the bagasse, and the drying temperature is 60 to 80°C.

[0015] Furthermore, the mesh size of the sieving in step (4) is 100-200 meshes, the lubricant is polydimethylsiloxane or polymethylphenylsiloxane, and the lubricant accounts for 10%-15% of the mass of the bagasse, and the vacuum drying temperature is 60-70°C.

[0016] The method for preparing the above-mentioned high-toughness and crack-resistant PP plastic comprises the following steps:

[0017] A1: Melt and mix PP and POE to form mixture A;

[0018] A2: The modified natural fiber toughening agent is mixed with glass fiber to form a solid mixture, the solid mixture and nano calcium carbonate are added to mixture A, and high-toughness and crack-resistant PP plastic is obtained by extruding on a twin-screw extruder.

[0019] Furthermore, in the step A1, the melting temperature is 150-170°C.

[0020] Furthermore, the extrusion temperature in step A2 is 180-190°C.

[0021] Furthermore, the high-toughness and crack-resistant PP plastic is used in three major fields: daily plastic products, small household appliances and films.

[0022] Beneficial effects of the present invention:

[0023] (1) Sugarcane bagasse is used as a natural fiber toughening agent. Boiling and fermenting sugarcane bagasse with water can change the fiber structure and decompose some of the binding agents. Lubricants are added during the preparation process to reduce friction between fibers, thereby improving fiber toughness.

[0024] (2) Natural fiber toughening agents are compounded with glass fibers to form bridges and support structures in composite materials, thereby strengthening the bonding force and improving the toughness of the overall material.

[0025] (3) Bagasse is used as a natural fiber toughening agent and mixed with PP. It has a low density, low cost, recyclability, and is environmentally friendly and pollution-free. DETAILED DESCRIPTION

[0026] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0027] Example 1

[0028] A high-toughness and crack-resistant PP plastic comprises the following raw materials in parts by weight: 50 parts of PP (polypropylene), 20 parts of POE (polyolefin elastomer), 15 parts of modified natural fiber toughening agent, 10 parts of glass fiber, and 10 parts of nano calcium carbonate.

[0029] The preparation method of the modified natural fiber toughening agent comprises the following steps:

[0030] (1) washing bagasse to remove impurities, adding water to heat and boiling;

[0031] (2) then cooling, adding a biological fermentation agent for fermentation, and obtaining a pre-product;

[0032] (3) adding a hydroxyl radical scavenger to the pre-product, mixing and stirring, filtering and drying to obtain product A;

[0033] (4) The product A is ground in a ball mill, sieved, added with a lubricant and stirred, and then vacuum dried to obtain a modified natural fiber toughening agent.

[0034] In the step (1), the mass ratio of bagasse to water is 2:3, the heating refers to heating to 98° C., and the boiling time is 20 minutes.

[0035] The cooling in step (2) refers to cooling to 30° C., the biological fermentation agent is yeast, and the yeast accounts for 1% of the mass of sugarcane bagasse, the fermentation temperature is 25° C., and the fermentation time is 5 days.

[0036] In the step (3), the hydroxyl radical scavenger is sodium borohydride, and the hydroxyl radical scavenger accounts for 2% of the mass of the bagasse, and the drying temperature is 60°C.

[0037] The mesh size of the sieving in the step (4) is 100 meshes, the lubricant is polydimethylsiloxane, and the lubricant accounts for 10% of the mass of the bagasse, and the temperature of the vacuum drying is 60°C.

[0038] The preparation method of high-toughness and crack-resistant PP plastic comprises the following steps:

[0039] A1: 50 parts by weight of PP and 20 parts by weight of POE were melt-mixed to form a mixture A;

[0040] A2: 15 parts by weight of a modified natural fiber toughening agent and 10 parts by weight of glass fiber are mixed to form a solid mixture, the solid mixture and 10 parts by weight of nano-calcium carbonate are added to mixture A, and extruded on a twin-screw extruder to obtain a high-toughness, crack-resistant PP plastic.

[0041] The melting temperature in step A1 is 150°C.

[0042] The extrusion temperature in step A2 is 180°C.

[0043] The high-toughness and crack-resistant PP plastic is used in three major fields: daily plastic products, small household appliances and films.

[0044] Example 2

[0045] A high-toughness and crack-resistant PP plastic comprises the following raw materials in parts by weight: 65 parts of PP (polypropylene), 27 parts of POE (polyolefin elastomer), 17 parts of modified natural fiber toughening agent, 13 parts of glass fiber, and 13 parts of nano calcium carbonate.

[0046] The preparation method of the modified natural fiber toughening agent comprises the following steps:

[0047] (1) washing bagasse to remove impurities, adding water to heat and boiling;

[0048] (2) then cooling, adding a biological fermentation agent for fermentation, and obtaining a pre-product;

[0049] (3) adding a hydroxyl radical scavenger to the pre-product, mixing and stirring, filtering and drying to obtain product A;

[0050] (4) The product A is ground in a ball mill, sieved, added with a lubricant and stirred, and then vacuum dried to obtain a modified natural fiber toughening agent.

[0051] In the step (1), the mass ratio of bagasse to water is 2:3, the heating refers to heating to 100° C., and the boiling time is 25 minutes.

[0052] The cooling in step (2) refers to cooling to 35° C., the biological fermentation agent is yeast, and the yeast accounts for 3% of the mass of sugarcane bagasse, the fermentation temperature is 30° C., and the fermentation time is 6 days.

[0053] In the step (3), the hydroxyl radical scavenger is sodium borohydride, and the hydroxyl radical scavenger accounts for 2.5% of the mass of the bagasse, and the drying temperature is 70°C.

[0054] The mesh size of the sieving in the step (4) is 150 meshes, the lubricant is polydimethylsiloxane, and the lubricant accounts for 13% of the mass of the bagasse, and the temperature of the vacuum drying is 65°C.

[0055] The preparation method of high-toughness and crack-resistant PP plastic comprises the following steps:

[0056] A1: 65 parts by weight of PP and 27 parts by weight of POE were melt-mixed to form a mixture A;

[0057] A2: 17 parts by weight of a modified natural fiber toughening agent and 13 parts by weight of glass fiber are mixed to form a solid mixture, the solid mixture and 13 parts by weight of nano-calcium carbonate are added to mixture A, and a high-toughness, crack-resistant PP plastic is obtained by extruding on a twin-screw extruder.

[0058] The melting temperature in step A1 is 160°C.

[0059] The extrusion temperature in step A2 is 185°C.

[0060] The high-toughness and crack-resistant PP plastic is used in three major fields: daily plastic products, small household appliances and films.

[0061] Example 3

[0062] A high-toughness and crack-resistant PP plastic comprises the following raw materials in parts by weight: 80 parts of PP (polypropylene), 35 parts of POE (polyolefin elastomer), 20 parts of modified natural fiber toughening agent, 15 parts of glass fiber, and 15 parts of nano calcium carbonate.

[0063] The preparation method of the modified natural fiber toughening agent comprises the following steps:

[0064] (1) washing bagasse to remove impurities, adding water to heat and boiling;

[0065] (2) then cooling, adding a biological fermentation agent for fermentation, and obtaining a pre-product;

[0066] (3) adding a hydroxyl radical scavenger to the pre-product, mixing and stirring, filtering and drying to obtain product A;

[0067] (4) The product A is ground in a ball mill, sieved, added with a lubricant and stirred, and then vacuum dried to obtain a modified natural fiber toughening agent.

[0068] In the step (1), the mass ratio of bagasse to water is 2:3, the heating refers to heating to 100° C., and the boiling time is 30 minutes.

[0069] The cooling in step (2) refers to cooling to 40° C., the biological fermentation agent is yeast, and the yeast accounts for 5% of the mass of sugarcane bagasse, the fermentation temperature is 35° C., and the fermentation time is 7 days.

[0070] In the step (3), the hydroxyl radical scavenger is sodium borohydride, and the hydroxyl radical scavenger accounts for 3% of the mass of the bagasse, and the drying temperature is 80°C.

[0071] The mesh size of the sieving in the step (4) is 200 meshes, the lubricant is polydimethylsiloxane, and the lubricant accounts for 15% of the mass of the bagasse, and the temperature of the vacuum drying is 70°C.

[0072] The preparation method of high-toughness and crack-resistant PP plastic comprises the following steps:

[0073] A1: 80 parts by weight of PP and 35 parts by weight of POE were melt-mixed to form a mixture A;

[0074] A2: 20 parts by weight of modified natural fiber toughening agent and 15 parts by weight of glass fiber are mixed to form a solid mixture, the solid mixture and 15 parts by weight of nano calcium carbonate are added to mixture A, and extruded on a twin-screw extruder to obtain a high-toughness and crack-resistant PP plastic.

[0075] The melting temperature in step A1 is 170°C.

[0076] The extrusion temperature in step A2 is 190°C.

[0077] The high-toughness and crack-resistant PP plastic is used in three major fields: daily plastic products, small household appliances and films.

[0078] Comparative Example 1

[0079] On the basis of Example 2, the step (2) of adding a biological fermentation agent for fermentation in the preparation process of the modified fiber toughening agent was removed, and the other conditions were consistent with those in Example 2.

[0080] Comparative Example 2

[0081] On the basis of Example 2, the lubricant added in step (4) during the preparation of the modified fiber toughening agent was removed, and the other conditions were consistent with those of Example 2.

[0082] Comparative Example 3

[0083] On the basis of Example 2, the high-toughness and crack-resistant PP plastic raw material component and the modified natural toughening agent in the preparation process are removed and replaced with an equal weight portion of glass fiber. Other conditions are consistent with Example 2.

[0084] Comparative Example 4

[0085] On the basis of Example 2, the high-toughness and crack-resistant PP plastic raw material component and the glass fiber in the preparation process are removed and replaced with an equal weight portion of modified natural toughening agent. Other conditions are consistent with Example 2.

[0086] 1. High toughness crack resistance test

[0087] Impact resistance test: Examples 1 to 3 and Comparative Examples 1 to 4 were made into standard specimens, the specifications of which were: 80 mm × 10 mm × 4 mm with a notch, a V-shaped notch, and a notch depth of 2 mm. The specimens were tested according to GB / T1043-93. Impact strength a k (kJ / m 2 ), the calculation formula is as follows:

[0088] a k =1000×A k / (bd k )

[0089] Where: A k —Impact energy absorbed by the notched specimen (J);

[0090] b—specimen width (mm);

[0091] d k —Remaining thickness of notched specimen (mm).

[0092] Tensile performance test: Examples 1 to 3 and Comparative Examples 1 to 4 were made into standard specimens, the specimen size was: 150 mm × 10 mm × 4 mm dumbbell-shaped standard specimens, the tensile speed was 50 mm / min, and the test temperature was room temperature. The tensile strength and elongation at break of the specimens were measured in accordance with GB / T 1040.1-2018.

[0093] Table 1 shows the test results of impact resistance, tensile strength and elongation at break.

[0094] Table 1 High toughness crack resistance test results

[0095] Sample <![CDATA[Impact strength / (kJ / m 2 )]]> Tensile strength / MPa Elongation at break / % Example 1 15.6 22.5 305 Example 2 16.2 21.9 312 Example 3 16.0 22.2 309 Comparative Example 1 12.3 26.8 241 Comparative Example 2 8.6 28.3 192 Comparative Example 3 13.8 25.9 261 Comparative Example 4 13.4 26.2 258

[0096] It can be seen from Table 1 that the impact strength and elongation at break of Examples 1 to 3 are greater than those of Comparative Examples 1 to 4, while the tensile strength is less than that of Comparative Examples 1 to 4. Bagasse is used as a natural fiber toughening agent, and the bagasse is boiled and fermented. Lubricants are added during the preparation process to reduce friction between fibers, change the fiber structure, and decompose part of the binding agent, thereby improving the fiber toughness. The natural fiber toughening agent is compounded with glass fiber to form a bridge and a supporting structure in the composite material, strengthen the binding force, and thereby improve the toughness of PP plastic.

[0097] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A high-toughness and crack-resistant PP plastic, characterized in that: The high-toughness and crack-resistant PP plastic comprises the following raw materials in parts by weight: 50-80 parts of PP, 20-35 parts of POE, 15-20 parts of modified natural fiber toughening agent, 10-15 parts of glass fiber, and 10-15 parts of nano calcium carbonate.

2. A high-toughness, crack-resistant PP plastic according to claim 1, characterized in that: The preparation method of the modified natural fiber toughening agent comprises the following steps: (1) washing bagasse to remove impurities, adding water to heat and boiling; (2) then cooling, adding a biological fermentation agent for fermentation, and obtaining a pre-product; (3) adding a hydroxyl radical scavenger to the pre-product, mixing and stirring, filtering and drying to obtain product A; (4) The product A is ground in a ball mill, sieved, added with a lubricant and stirred, and then vacuum dried to obtain a modified natural fiber toughening agent.

3. A high-toughness and crack-resistant PP plastic according to claim 2, characterized in that: In the step (1), the mass ratio of bagasse to water is 2:3, the heating refers to heating to 98-100° C., and the boiling time is 20-30 minutes.

4. The high-toughness and crack-resistant PP plastic according to claim 2, characterized in that: The cooling in step (2) refers to cooling to 30-40° C., the biological fermentation agent is yeast, and the yeast accounts for 1%-5% of the mass of sugarcane bagasse, the fermentation temperature is 25-35° C., and the fermentation time is 5-7 days.

5. The high-toughness and crack-resistant PP plastic according to claim 2, characterized in that: In the step (3), the hydroxyl radical scavenger is potassium permanganate or sodium borohydride, and the hydroxyl radical scavenger accounts for 2% to 3% of the mass of the bagasse, and the drying temperature is 60 to 80°C.

6. The high-toughness and crack-resistant PP plastic according to claim 2, characterized in that: The mesh size of the sieving in the step (4) is 100-200 meshes, the lubricant is polydimethylsiloxane or polymethylphenylsiloxane, and the lubricant accounts for 10%-15% of the mass of the bagasse, and the vacuum drying temperature is 60-70°C.

7. A method for preparing a high-toughness, crack-resistant PP plastic according to any one of claims 1 to 6, characterized in that: The preparation method of the high-toughness and crack-resistant PP plastic comprises the following steps: A1: Melt and mix PP and POE to form mixture A; A2: The modified natural fiber toughening agent is mixed with glass fiber to form a solid mixture, the solid mixture and nano calcium carbonate are added to mixture A, and high-toughness and crack-resistant PP plastic is obtained by extruding on a twin-screw extruder.

8. The method for preparing a high-toughness and crack-resistant PP plastic according to claim 7, characterized in that: The melting temperature in step A1 is 150-170°C.

9. The method for preparing a high-toughness and crack-resistant PP plastic according to claim 7, characterized in that: The extrusion temperature in step A2 is 180-190°C.

10. The high-toughness and crack-resistant PP plastic according to claim 1, characterized in that: The high-toughness and crack-resistant PP plastic is used in three major fields: daily plastic products, small household appliances and films.

Citation Information

Patent Citations

  • Low-warpage, scratch-resistant and soft-touch modified polypropylene composite material and preparation method thereof

    CN114316434A

  • Antibacterial glass fibre / nanometer particle / polypropylene composite material and production thereof

    CN1712445A

  • Reinforced toughening anti-aging polypropylene / nano calcium carbonate composite material and its preparation method

    CN1966564A